(untitled) (Iranian Journal of Kidney Diseases, 2014)
Candida infection in the small intestine is uncommon. We report an unusual case of duodenal candidiasis that presented as chronic diarrhea in a patient who had previously undergone kidney transplantation. A 60-year-old man presented with profuse watery diarrhea that had lasted 6 months 13 years after kidney transplantation. Upper gastrointestinal endoscopy results indicated candidiasis within the esophagus and duodenum. Biopsy results revealed active duodenitis with hyphal and yeast forms of Candida overlying the duodenal epithelium in periodic acid Schiff staining. The patient was successfully treated with fluconazole. After 6 months of follow-up, the patient had no complaint of diarrhea. Duodenal candidiasis may be the result of chronic diarrhea in patients with a history of kidney transplantation.